Kinetic properties of extracellular thermophilic naringinase produced by rhizophus stolonifer isolated from palmyrah fruit pulp - Sinthuja, K.; Kapilan, R.; Vasantharuba, S. (University of Jaffna, 2017)
Bitterness of the fruit juices is a serious challenge in the processing of fruit juices in the food industries. Debittering of the juice using the enzyme naringinase produced by diverse microbes naturally is a promising approach, as it causes minimal damage to the nutritional quality and enhances organoleptic properties. Since Naringinase is an expensive enzyme widely used in the food industry, there is scope for fermentation process development using new isolates, which would result in commercially viable processes. Rhizophus stolonifer was isolated from Palmyrah fruit pulp and the extracellular naringinase enzyme was characterized. The crude naringinase enzyme was highly active at 65ºC and it was very stable at 60ºC for at least one hour. Highest naringinase activity was obtained at pH 4.0 and the enzyme was stable at pH 4.5 for at least one hour. The enzyme showed zero order kinetics for 10 minutes. Vmax of the crude naringinase enzyme was 3.125 µmol/mL and Michaelis constant by Lineweaver-Burk Plot for naringin was 3.076 mg/mL under the conditions. Metal ions Mn2+, Cu2+ and Ba2+ increased the naringinase enzyme activity but Mg2+, Zn2+, Hg2+, Ca2+ and Na+ reduced the enzyme activity. Naringinase was more stable with Cu2+ than Mn2+ and Ba2+. The optimum conditions for naringinase activity can be achieved at 65oC and at pH 4.0 and the enzyme is stable for at least one hour. Therefore the naringinase enzyme from Rhizophus stolonifer isolated from palmyrah fruit pulp could be an ideal candidate for the debittering of acidic food items that are produced using moderately high temperatures in the food industries.
Keywords: Debittering; Kinetic properties; Michaelis constant; Naringinase; Palmyrah pulp; Rhizophus stolonifera